EMPOWERMENT FARMERS LAND THROUGH CONSERVATION SOIL TECHNIQUES WITH VEGETATIVE METHODS - Yusra Yusra; Nasruddin Nasruddin; Hendrival Hendrival; Khusrizal Khusrizal; Baidhawi Baidhawi; Muhammad Nazaruddin (LPPM dan PM Universitas Samudra, 2022)
The problem on physical properties of land in Reuleut Timu Village is that topography varies from flat, wavy, and sloping. As a different topography, depth water varies as well, some are shallow and deep. The depth of tillage is shallow and has a dense layer, lack of water, low organic matter, generally has a structure soil dense. The purpose of community service activities is to increase motivation partner farmers use abandoned land, increase conservation soil and income from partner farmers, guide farmers to utilize waste agricultural as compost and intercropping. Methods of community service activities are counseling, practices composting, and intercropping. The results that showed to activity can be said effective because activity has been running according to purpose activity. Partners gain knowledge and skills about manufacture and application of straw compost and intercropping, which are soil conservation techniques using method vegetative. Conservation soil can increase fertility soil with increase income farmers' by making straw compost.